The role of lipids in determining the air-water interfacial properties of wheat, rye, and oat dough liquor constituents. (30th July 2020) - Janssen, Frederik; Wouters, Arno G.B.; Linclau, Lize; Waelkens, Etienne; Derua, Rita; Dehairs, Jonas; Moldenaers, Paula; Vermant, Jan; Delcour, Jan A.
Highlights: Dough liquor (DL) was isolated from fermented wheat, rye, and oat doughs. Their lipid species populations were determined with mass spectrometry. Air-water interfacial properties of control and defatted DL constituents were compared. Proteins and lipids co-exist at wheat and rye DL stabilized air-water interfaces. Lipids are the predominant constituent at oat DL stabilized air-water interfaces. Abstract: Bread is mainly made from wheat but also from other cereals such as rye and oats. We here report on the role of dough liquor (DL) proteins and lipids in determining the stability of gas cell air-water (A-W) interfaces in wheat, rye, and oat bread making. Surprisingly, most lipids in DLs of these cereals are nonpolar. Their main polar DL lipids are phospholipids. Lipids at wheat and rye DL stabilized A-W interfaces impair interactions between its proteins, as reflected by an increased A-W interfacial shear viscosity of the adsorbed film upon defatting. In contrast, removing most lipids from oat DL pronouncedly increased the A-W interface surface tension, demonstrating that lipids are the prominent adsorbed species.